Evaluating the ecological hypothesis: early life salivary microbiome assembly predicts dental caries in a longitudinal case-control study - Freida Blostein; Deesha Bhaumik; Elyse Davis; Elizabeth Salzman; Kerby Shedden; Melissa Duhaime; Kelly M. Bakulski; Daniel W. McNeil; Mary L. Marazita; Betsy Foxman (Microbiome, 2022)
Abstract Background Early childhood caries (ECC)—dental caries (cavities) occurring in primary teeth up to age 6 years—is a prevalent childhood oral disease with a microbial etiology. Streptococcus mutans was previously considered a primary cause, but recent research promotes the ecologic hypothesis, in which a dysbiosis in the oral microbial community leads to caries. In this incident, density sampled case-control study of 189 children followed from 2 months to 5 years, we use the salivary bacteriome to (1) prospectively test the ecological hypothesis of ECC in salivary bacteriome communities and (2) identify co-occurring salivary bacterial communities predicting future ECC. Results Supervised classification of future ECC case status using salivary samples from age 12 months using bacteriome-wide data (AUC-ROC 0.78 95% CI (0.71–0.85)) predicts future ECC status before S. mutans can be detected. Dirichlet multinomial community state typing and co-occurrence network analysis identified similar robust and replicable groups of co-occurring taxa. Mean relative abundance of a Haemophilus parainfluenzae/Neisseria/Fusobacterium periodonticum group was lower in future ECC cases (0.14) than controls (0.23, P value < 0.001) in pre-incident visits, positively correlated with saliva pH (Pearson rho = 0.33, P value < 0.001) and reduced in individuals who had acquired S. mutans by the next study visit (0.13) versus those who did not (0.20, P value < 0.01). In a subset of whole genome shotgun sequenced samples (n = 30), case plaque had higher abundances of antibiotic production and resistance gene orthologs, including a major facilitator superfamily multidrug resistance transporter (MFS DHA2 family P BH value = 1.9 × 10−28), lantibiotic transport system permease protein (P BH value = 6.0 × 10−6) and bacitracin synthase I (P BH value = 5.6 × 10−6). The oxidative phosphorylation KEGG pathway was enriched in case plaque (P BH value = 1.2 × 10−8), while the ABC transporter pathway was depleted (P BH value = 3.6 × 10−3). Conclusions Early-life bacterial interactions predisposed children to ECC, supporting a time-dependent interpretation of the ecological hypothesis. Bacterial communities which assemble before 12 months of age can promote or inhibit an ecological succession to S. mutans dominance and cariogenesis. Intragenera competitions and intergenera cooperation between oral taxa may shape the emergence of these communities, providing points for preventive interventions. Video Abstract